Ben Behind His Voices: One Family's Journey from the Chaos of Schizophrenia to Hope - Kaye, Randye (Rowman & Littlefield Publishers, 2011)
When readers first meet Ben, he is a sweet, intelligent, seemingly well-adjusted youngster. Fast forward to his teenage years, though, and Ben's life has spun out of control. Ben is swept along by an illness over which he has no control—one that results in runaway episodes, periods of homelessness, seven psychotic breaks, seven hospitalizations, and finally a diagnosis and treatment plan that begins to work. Schizophrenia strikes an estimated one in a hundred people worldwide by some estimates, and yet understanding of the illness is lacking. Through Ben's experiences, and those of his mother and sister, who supported Ben through every stage of his illness and treatment, readers gain a better understanding of schizophrenia, as well as mental illness in general, and the way it affects individuals and families. Here, Kaye encourages families to stay together and find strength while accepting the reality of a loved one's illness; she illustrates, through her experiences as Ben's mother, the delicate balance between letting go and staying involved. She honors the courage of anyone who suffers with mental illness and is trying to improve his life and participate in his own recovery. Ben Behind His Voices also reminds professionals in the psychiatric field that every patient who comes through their doors has a life, one that he has lost through no fault of his own. It shows what goes right when professionals treat the family as part of the recovery process and help them find support, education, and acceptance. And it reminds readers that those who suffer from mental illness, and their families, deserve respect, concern, and dignity.